Recurrent dislocation of the extensor carpi ulnaris tendon. Issue 2 (June 1998) - Inoue, G; Tamura, Y
Abstract : Five patients with recurrent dislocation of the extensor carpi ulnaris (ECU) tendon resulting from an athletic injury were treated by reconstruction of the ECU tendon sheath, and each had a satisfactory result. Two types of disruption of the fibro-osseous sheath were found. In two cases in which the fibro-osseous sheath ruptured radially, the torn sheath lay on its ulnar groove beneath the ECU tendon. These patients were treated by direct suture of the sheath over the ECU tendon. In three cases in which the fibro-osseous sheath ruptured ulnarly, the torn sheath lay superficial to the ECU tendon. These patients were treated by reconstruction of the sheath using a piece of the extensor retinaculum. We believe that surgical reconstruction of the fibro-oseous sheath of the ECU tendon should be considered for symptomatic dislocation of the ECU tendon, even in an acute case.